Comparison of umami taste peptides in water-soluble extractions of Jinhua and Parma hams. Issue 2 (March 2015) - Dang, Yali; Gao, Xinchang; Ma, Fumin; Wu, Xueqian
Abstract: Peptides are critical to the taste of dry-cured ham. To isolate and identify umami peptide fractions from the water-soluble extractions (WSEs) of Jinhua and Parma hams, separation procedures utilizing Sephadex G-25 and reversed-phase high-performance liquid chromatography (RP-HPLC) were combined with sensory evaluations (taste dilution analysis and an electronic tongue). The amino acid sequences of the umami peptides, Cys-Cys-Asn-Lys-Ser-Val (CCNKSV) from Jinhua ham and Ala-His-Ser-Val-Arg-Phe-Tyr (AHSVRFY) from Parma ham, were identified by MALDI-TOF-MS; subsequently, both were synthesized, and their umami taste properties were evaluated. The results indicate that the tastes of the umami peptides were similar to those of the hams' WSEs. Highlights: The umami peptide Cys-Cys-Asn-Lys-Ser-Val from Jinhua ham was identified. The umami peptide Ala-His-Ser-Val-Arg-Phe-Tyr from Parma ham was identified. The umami taste properties of peptides were evaluated similar to the ham's WSE.